Integration of securities market infrastructures in the euro area - Heiko Schmiedel; Andreas Schönenberger (European Central Bank (ECB), 2005)
This paper investigates the state and process of integration of the European securities market infrastructure. The integration of financial infrastructures is one of the basic policy goals and key responsibilities of the Eurosystem. The paper finds that, despite the single currency, the euro area securities infrastructure remains highly fragmented and insufficiently integrated. There are still a high number of providers for trading, clearing and settlement, and they are not efficiently connected to one another. The paper also finds that the degree of consolidation varies among different integrated groups of market infrastructure. Economies of scale and scope and positive network externalities inherent in the securities services industry mean that substantial cost savings and increased efficiency can be expected from further integration. The most relevant factors underlying the less advanced areas of integration are likely to be not only persistent cross-border differences in tax regimes, procedures and laws, but also vested interests among users, owners and managers. Current work at the Eurosystem level can be expected to be helpful in promoting further integration.
Keywords: 330; Wertpapier; Wertpapierhandel; Finanzmarkt; Institutionelle Infrastruktur; Eurozone; EU-Staaten